Effect of clindamycin vaginal pessary before cesarean section on postpartum infectious morbidity - Mostafa Salem; Al-Zahraa Soliman; Islam Ammar (Microbes and Infectious Diseases, 2022)
Background: Post-cesarean section (CS) infections, namely, endometritis, fever and wound infection are considered a major health problem which necessitates effective interventions. Antibiotic prophylaxis before CS cannot completely eliminate the risk of postpartum infections. Preoperative antiseptic vaginal cleansing is one of the commonest methodsto reduce infectious morbidities after CS. Aim of the work: The aim of this work is to evaluate the effect of prophylactic administration of clindamycin vaginal suppository before elective CS on postpartum infectious morbidity. Methods: 196 patients were included in this intervention. They were divided equally into two groups (each 98 patients); intervention group (which received clindamycin 100 mg vaginal suppository at bedtime for 3 nights before CS) and control group (which received nothing). Both groups were followed till the end of puerperium for the development of postpartum infections namely, endometritis, fever, and wound infection. Results: There was statistically significant decrease in the frequency of endometritis, fever, and wound infection in the intervention group when compared to control group. Also, there was highly statistically significant decrease in the frequency of overall post-CS infectious morbidity in the intervention group when compared to control group. There was statistically significant difference between both groups as regard white blood cells count and C-reactive protein level 24 hours after cesarean section. Conclusion: Prophylactic administration of clindamycin vaginal suppository before elective CS reduces the risk of postpartum infections namely endometritis, fever, wound infection and overall post-CS infectious morbidity. Preoperative clindamycin vaginal suppository could be  protective against post-CS infectious morbidities.